Entwicklungen in Slavischen Sprachen 2 Fuer Volkmar Lehmann zum 60. Geburtstag von seinen Schuelerinnen und Schuelern - Anstatt, Tanja; Hansen, Björn (Specimina philologiae Slavicae, 2003)
This volume is dedicated to Volkmar Lehmann's 60th birthday. At the same time the book offers us the opportunity to present a small synopsis of the work of the Jubilee and to express our appreciation of these works by each of the articles takes up a thesis by Volkmar Lehmann. The articles assembled here also receive a contextual connection in that the question of linguistic development plays a role in them. At the same time, the title "Developments in Slavic Languages ​​2" links up with a previous anthology of the same title. While articles on diachronic issues are summarized in the first volume, this is a broader concept of the concept of development.